2021
DOI: 10.52547/ijree.6.4.57
|View full text |Cite
|
Sign up to set email alerts
|

Error Analysis of Taiwanese University Students’ English Essay Writing: A Longitudinal Corpus Study

Abstract: Writing is considered one of the most difficult skills in EFL/ESL. Thus, meticulous recognition and classification of students' errors in certain contexts is a worthwhile endeavor which provides us with both diagnostic and prognostic power. Accordingly, a total of 430 students in 15 English writing classes held during 12 consecutive semesters in a private university in central Taiwan were the subjects of this study. They composed 5703 essays which were rated and coded by the authors. Adopting and modifying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…• Autocorrection: Certain errors are automatically corrected by the software without the author's knowledge, resulting in erroneous analyses. While explaining reasons for not employing software for EA, Shirban Sasi [67] mentioned that the software may automatically rectify various problems, such as spelling, punctuation, and even word choice, without the researcher's knowledge. A study by Barrot [32] employing Grammarly required learners to turn off the autocorrect feature as protocol to prevent the software from prescreening the text.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…• Autocorrection: Certain errors are automatically corrected by the software without the author's knowledge, resulting in erroneous analyses. While explaining reasons for not employing software for EA, Shirban Sasi [67] mentioned that the software may automatically rectify various problems, such as spelling, punctuation, and even word choice, without the researcher's knowledge. A study by Barrot [32] employing Grammarly required learners to turn off the autocorrect feature as protocol to prevent the software from prescreening the text.…”
mentioning
confidence: 99%
“…Misleading Feedback: CBEA as employed in grammar checkers often provides corrective feedback to correct erroneous words or sentences. However, researchers employing Grammarly, CYWrite, and Write&Improve found that, on certain occasions, the feedback given could divert the meaning of the sentence; this situation occurred when the suggested answers were not suitable with respect to the intentions of the sentence [33,45,67]. The feedback provided by Grammarly is not in line with the intentions of the users [27,42,68].…”
mentioning
confidence: 99%